Treatment Methods and Early Neurologic Improvement After Endovascular Treatment of Tandem Occlusions in Acute Ischemic Stroke - Wallocha, Marta; Chapot, René; Nordmeyer, Hannes; Fiehler, Jens; Weber, Ralph; Stracke, Christian Paul (Frontiers in Neurology, 2019)
Background and Purpose: A tandem occlusion of the intracranial circulation and the extracranial carotid artery (ICA) occurs in 10–20% of all strokes based on large vessel occlusion (LVO). The optimal treatment strategy for those patients is unknown. We report our management strategy and the outcome in these patients in a large single-center cohort. Materials and Methods: We retrospectively identified and analyzed all patients treated by Mechanical Thrombectomy (MT) for an intracranial LVO associated with an occlusion of the extracranial ICA between April 2009 and May 2016 (163/1,645, 9.9%). The following data was collected: Recanalization rate, occurrence of symptomatic intracranial hemorrhage (sICH), clinical result according to the early neurological improvement (ENI, NIHSS score improvement of ≥8 points after 24 h or NIHSS score of 0 or 1 after 3 days) and functional outcome and mortality during long term follow up. Secondary endpoints were the patency of the internal carotid artery at 24 h. Patient demographics and anti-aggregation regimen were recorded as co-variables. Results: 163/1,645 (9.9%) MT patients had a tandem occlusion. All thrombectomy procedures were performed with stent retrievers. PTA with or without additional placement of a stent was performed in 149 vs. 14 patients. The overall rate of TICI IIB/III recanalization was 91.4%. An early neurological improvement was found in 79 of 163 patients (48.4%), 51% (76/149) in the stent group and 21% (3/14) in the non stent group. 120/163 patients (73.6%) had a long term favorable outcome (mRS 0–2). The ICA re-occlusion rate at 24 h was 5.4% (8/149) in the stent group and 42% (6/14) in the non stent group. The rate of symptomatic hemorrhage was 4.9%. The regression analysis showed that only younger age (p = 0.002) and shorter recanalization times (p = 0.017) were associated with good outcome. Conclusion: Stent-PTA of the ICA in addition to MT with a stent retriever was safe and effective in tandem occlusion of the anterior brain circulation. PTA and MT without stenting in tandem lesions showed a higher early re-occlusion rate and lower rate of early neurological improvement. The technical approach should aim for the fastest possible recanalization of the intracranial vessels, either with stenting first or last.